Radar Banten's Strategy in Facing the Era of Media Digitalization - Ramadhan, Aditya; Dimyati, Idi; Yusanto, Yoki; Muldi, Ail; Kurniawati, Rd Nia Kania (Jurnal Ilmiah Global Education, 2024)
Newspaper readers continue to decline and slowly shift to using digital media platforms to obtain information. This happens along with the development of information technology where many online media, social media and so on have emerged. The task and challenge of the print media is to expand its presence into the realm of new media, while continuing to guard the accuracy, credibility and trust that have been the hallmarks of mainstream media. The proliferation of the internet, which is increasingly accessible, has made the media convergence movement grow in particular. Media convergence also occurs in Radar Banten as one of the media that exists in the national arena. This research aims to find out the strategy of Radar Banten Daily to transform itself towards media convergence. The study, which is a qualitative research adopting a constructive paradigm, collected data through interviews and literature review. This research investigates the application of media convergence concept by Radar Banten in facing modern media transformation. Three convergence models, namely newsroom convergence, news gathering convergence, and content convergence, are analyzed as an effort to unify media operations through a holistic approach. The result of the research shows that the 3M strategy (multimedia, multichannel, multiplatform) allows Radar Banten to increase its content coverage, create inter-platform synergy, and strengthen their position in the midst of technological development. The editorial work pattern underwent significant changes, with projection meetings conducted online and deadline adjustments to support online and social media. Overall, this research concludes that Radar Banten is progressively adapting and innovating to stay relevant amidst mass media changes. The continuity of this effort is the key to their success in facing the dynamics of modern media.